1985
DOI: 10.1007/bf02388603
|View full text |Cite
|
Sign up to set email alerts
|

Sternal ossification in normal newborn infants

Abstract: The lateral chest radiographs of 200 Nigerian newborn infants, whose gestational age was estimated by the Dubowitz examination, were analysed for the pattern of ossification of sternal segments. The length of each visible centre was also measured. The manubrium was ossified in all infants over 35 weeks. All infants 37 weeks and above demonstrated ossification of the first and second mesosternal segments. Ten infants had ossification of the xiphisternum. The average number of ossified segments seen in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…McCormick & Nichols reported that ossification begins in manubrium and progresses to mesosternal (body) segments, presenting cranial to caudal development. The manubrium is reported to ossify first, in the 6 th fetal month (Kozielec, 1973;Kim et al, 1981;Odita et al, 1985;O'Neal et al, 1998). The mesosternum is reported to ossify in a craniocaudal direction, with ossification occurring first in segment 2 and last in segment 4.…”
Section: Discussionmentioning
confidence: 99%
“…McCormick & Nichols reported that ossification begins in manubrium and progresses to mesosternal (body) segments, presenting cranial to caudal development. The manubrium is reported to ossify first, in the 6 th fetal month (Kozielec, 1973;Kim et al, 1981;Odita et al, 1985;O'Neal et al, 1998). The mesosternum is reported to ossify in a craniocaudal direction, with ossification occurring first in segment 2 and last in segment 4.…”
Section: Discussionmentioning
confidence: 99%
“…The mesosternum is reported to ossify in a craniocaudal direction, with ossification occurring first in segment 2 and last in segment 4 (1)(2)(3)(4)(5)(6)(7)(8)(9). Ossification is reported to be present at birth (1)(2)(3)(4)(5)(6)(7)(8)(9). In this series, asynchronous nonossified sternal segments were observed in 3.5% of subjects, occurring most commonly at the second (superior mesosternal) and fourth (inferior mesosternal) segments.…”
Section: Discussionmentioning
confidence: 98%
“…The manubrium is reported to ossify first, in the 6th fetal month (1)(2)(3)(4)(5)(6)(7)(8)(9). The mesosternum is reported to ossify in a craniocaudal direction, with ossification occurring first in segment 2 and last in segment 4 (1)(2)(3)(4)(5)(6)(7)(8)(9). Ossification is reported to be present at birth (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations